A box model for representing estuarine physical processes in Earth system models. (April 2017) - Sun, Qiang; Whitney, Michael M.; Bryan, Frank O.; Tseng, Yu-heng
Highlights: An analytic Estuary Box Model (EBM) is proposed to better represent the riverine freshwater flux in climate models. The EBM is parameterized by physical based mixing processes and implemented globally into the Community Earth System Model. The estuarine exchange flows have impacts on the global salinity field in both costal and open oceans. Abstract: Appropriately treating riverine freshwater discharge into the oceans in Earth system models is a challenging problem. Commonly, the river runoff is discharged into the ocean models with zero salinity and arbitrarily distributed either horizontally or vertically over several grid cells. Those approaches entirely neglect estuarine physical processes that modify river inputs before they reach the open ocean. In order to realistically represent riverine freshwater inputs in Earth system models, a physically based Estuary Box Model (EBM) is developed to parameterize the mixing processes in estuaries. The EBM represents the estuary exchange circulation with a two-layer box structure. It takes as input the river volume flux from the land surface model and the subsurface salinity at the estuary mouth from the ocean model. It delivers the estuarine outflow salinity and net volume flux into and out of the estuary to the ocean model. An offline test of the EBM forced with observed conditions for the Columbia River system shows good agreement with observations of outflow salinity and high-resolution simulations of the exchange flow volume flux. To illustrate the practicality of use of the EBM in an Earth system model, the EBM is implemented for all coastal grid cells with river runoff in the Community Earth System Model (CESM). Compared to the standard version of CESM, which treats runoff as an augmentation to precipitation, the EBM increases sea surface salinity and reduces stratification near river mouths. The EBM also leads to significant regional and remote changes in CESM ocean surface salinities.